Assessment of the efficacy of a video-based hybrid teaching module of oxygen therapy and critical care area troubleshooting in nursing professionals managing COVID-19 patients - Mridul Dhar; Sameer Sharma; K Hemanthkumar; Shalinee Rao (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Video-based teaching has become rapidly popular during the coronavirus disease 2019 (COVID-19) pandemic. The current study aimed to assess the efficacy of a hybrid video-based teaching module of oxygen therapy and critical care troubleshooting in nursing professionals managing COVID-19 patients in our institute. MATERIALS AND METHODS: A retrospective analytical study (pretest and posttest design) was conducted in our medical education department in March 2022 using the data from a workshop conducted on oxygen therapy and critical care area troubleshooting during COVID-19 patient management for 296 nursing professionals. A hybrid video-based teaching module was used. Pretest and posttest data were compared along with subgroup analysis. P value <0.05 was considered significant. RESULTS: Posttest scores were significantly higher than the baseline scores in the overall group as well as in all subgroups (P < 0.001). Subgroup comparisons revealed no significant difference in mean baseline pretest and posttest scores in male versus female participants. Baseline pretest scores (P = 0.02) and posttest scores (P = 0.08) were lower in the nurses of the noncritical areas compared to critical area nurses. Mean improvement in posttest score compared to baseline score was similar between all groups. CONCLUSION: Hybrid technique involving both video aspects and in-person teacher presence for demonstration or troubleshooting improves perceived knowledge in nursing professionals with some prior formal training and may be superior to the conventional only didactic/lecture-based demonstrations, especially in the context of imparting rapid training during pandemics or similar urgent situations.